THE RECONSTRUCTION OF THE ROLE OF ISLAM IN INDONESIA AS A PROPETHIC RELIGION - Naupal, Naupal (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2014)
After the end of Soehartoâs regime, in 52Â districts produced 78 regulations (perda) influencedÂ by sharia to purify Islam from secular institutions. Because of that, Islam in Indonesia now is criticized as having a tendency to be close to status quo, and resulting so many problems, such as being injustice and dehumanize. Islam as a prophetic religion, as a religion not only for faith to Allah, isÂ also a religion that liberating people from violence and injustice, as Prophet MuhammadÂ brought it. This academic writing , using the hermeneuticmethodÂ fromPaul Ricoeur, analizes the situation, by proposing three ways outthrough the theory of critical ideology,Â andÂ the deconstruction, andÂ offering to accept plurality, to overcome the problems of complicated situation. Propethic religion might be the proper solution for the problems of Islam in Indonesia than priestly/institutional religion, in order to acheive the better Indonesian society, by practising tolerance, openess in mind, egaliter and democatic.—–Setelah berakhirnya rezim Soeharto, 52 wilayahÂ membuat 78 perda syariâah yang menginginkanÂ pelaksanaan Islam secara kaffah. Oleh karena itu Islam di Indonesia dikritik sebagai agama yang cenderung berada dalam status qua, dan mengakibatkan munculnya banyakÂ masalah, seperti masalah ketidakadilan dan dehumanisasi.Â Islam sebagai sebuahÂ agama prophetis , hakikatnya tidak hanya bicara tentang keimananÂ kepada Tuhan, tetapi juga membahas tentang pembebasan manusia dari tindak kekerasaan dan ketidakadilan. Tulisan ini menggunakan metode hermeneutika dari Paul Ricoeur, yang berusaha menganalisis situasi di atas dengan mengajukan tiga pendekatan, yaitu kritik ideology, dekonstruksi, dan tawaran menerimaÂ prinsip pluralitas sebagai jalan keluar dari masalah yang komplek di Indonesia. AgamaÂ prophetisÂ diharapkan dapat menjadiÂ solusi menyeluruh bagi Â Â problem keagamaan (Islam) di Indonesia, sehingga terwujud masyarakat Indonesia yang toleran, terbuka, dan demokratis.Â